Public relations techniques and inter-institutional cooperation of Women Information Centers in Quezon City - Ocampo, Mary Anne Charmaine Stephanie F.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study aims to know the present public relations status of six resource centers with regards to users and other information centers, to know what benefits each information center gain from inter-institutional cooperation, and to improve the information centers' usage and efficiency. The descriptive research method was used. Data was gathered through questionnaires, interviews, and document analysis.
The study found that the information centers make use of public relations techniques but have no concrete public relations programs. The most common promotion of the information centers is through personal publicity but the most effective technique for bringing the users to the resource centers are websites, promotions through publications, and referral. Referral service, avoiding of duplication of materials, access to bibliographic resources and sharing of expertise are among the benefits that each center gains from inter-institutional cooperation. These help develop and maintain the information centers.
The resource centers must put serious effort and commitment in promoting the utilization of their collection and services. They must address their problems in public relations techniques so the whole organization will realize the importance of attracting users to utilize their collection and services.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- Public relations techniques; Library cooperation -- Philippines; Special libraries -- Philippines -- Quezon City